2002
DOI: 10.1055/s-2002-20556
|View full text |Cite
|
Sign up to set email alerts
|

Zur Praxis der stationären Asthmaschulung in der Bundesrepublik Deutschland - eine bundesweite Bestandsaufnahme

Abstract: While substantial advances in the proposition of patient education and self-management trainings in in-patient health care remain unquestioned, there are some deficits in actually performing such programs in clinical practice. Results also show that another question needs to be addressed: qualifying trainers. Less than half of trainers participating in this study reported to have absolved a train-the-trainer-course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
2
0
5
Order By: Relevance
“…Education programs vary in their content, often include multiple components across multiple sessions and may also include individual psychophysiological control interventions (such as relaxation, breathing techniques) and/or life style interventions (exercise, diet) (Mühlig et al, 2002). Documentation of educational content was suboptimal in many of the earlier trials (Sudre, Jacquemet, Uldry, & Perneger, 1999).…”
Section: Behavioral Medicine Treatment Approaches For Asthmamentioning
confidence: 99%
“…Education programs vary in their content, often include multiple components across multiple sessions and may also include individual psychophysiological control interventions (such as relaxation, breathing techniques) and/or life style interventions (exercise, diet) (Mühlig et al, 2002). Documentation of educational content was suboptimal in many of the earlier trials (Sudre, Jacquemet, Uldry, & Perneger, 1999).…”
Section: Behavioral Medicine Treatment Approaches For Asthmamentioning
confidence: 99%
“…Finally, three educational variants were ranked according to extent and intensity (training for outpatients was considered to correspond to the basic model for inpatients): From several other studies on the structure and supply of asthma education in rehabilitation centres and outpatient settings, we found that asthma education programmes are well established and considered an essential part of pulmonary rehabilitation in Germany [24]. However, the quality of asthma education or sections of a particular programme differs from clinic to clinic.…”
Section: Interventionsmentioning
confidence: 99%
“…Nach einer Untersuchung von Petro [8] wurden in weniger als 20 % der befragten pneumologischen Einrichtungen evaluierte Schulungsprogramme eingesetzt, w ä hrend die ü berwiegende Mehrheit der Schuler Materialien der Pharmaindustrie oder selbst entwickelte Schulungen benutzte, deren Eff ektivit ä t wissenschaftlich nicht belegt ist. 90,8 % der befragten Klinken gaben in einer Studie von M ü hlig et al [9] an, sich bei der Schulungsdurchf ü hrung an Expertenempfehlungen zu orientieren, bei genauerer Betrachtung bestanden jedoch deutliche Defi zite bei der Umsetzung dieser Qualit ä tsstandards. Evaluierte Schulungsprogramme wurden in 50 % der befragten Kliniken eingesetzt, w ä hrend die andere H ä lfte der Einrichtungen wissenschaftlich nicht gepr ü fte Schulungen durchf ü hrte (insbesondere Eigenentwicklungen); lediglich in 19 % der F ä lle wurden Schulungen entsprechend der jeweiligen Programminstruktionen praktiziert (Treatment-Integrit ä t).…”
unclassified
“…Tab 9. Ergebnisse der Teilnehmer-Beurteilung pro Modul: Informiertheit ü ber das Thema (Prozentangaben).…”
unclassified